2019
DOI: 10.1177/0020852319842661
|View full text |Cite
|
Sign up to set email alerts
|

Local government strategies in the face of shocks and crises: the role of anticipatory capacities and financial vulnerability

Abstract: Local government strategies in the face of shocks and crises. The role of anticipatory capacities and financial vulnerability

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 42 publications
1
25
0
2
Order By: Relevance
“…Whereas extant research into the financial resilience of local government has been conducted against the background of austerity, which focused on gradual adaptive processes and evolving financial management capabilities (Barbera et al, 2016(Barbera et al, , 2017(Barbera et al, , 2019Papenfuß et al, 2017;Steccolini et al, 2017), this paper explores the concept of financial resilience in local government in the context of the sudden nationwide COVID-19 pandemic. The pandemic requires a significant level of central government support, at least as an interim measure.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas extant research into the financial resilience of local government has been conducted against the background of austerity, which focused on gradual adaptive processes and evolving financial management capabilities (Barbera et al, 2016(Barbera et al, , 2017(Barbera et al, , 2019Papenfuß et al, 2017;Steccolini et al, 2017), this paper explores the concept of financial resilience in local government in the context of the sudden nationwide COVID-19 pandemic. The pandemic requires a significant level of central government support, at least as an interim measure.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the previous findings from multiple case studies, the stratified sampling in this large-scale quantitative survey assessed the make-up and the level of financial resilience dimensions, as well as their relation to financial and non-financial local government performance within and across three European countries. It also traced some interesting differences in local government financial resilience between the surveyed country contexts (Steccolini et al 2018;Barbera et al 2019).…”
Section: Evolution Of (Empirical) Financial Resilience Researchmentioning
confidence: 97%
“…The multiple case studies identified and operationalized the dimensions of financial resilience and highlighted that the patterns are the result of the interplay and development of different internal and external dimensions over time. Consequently, the financial resilience framework (Barbera et al 2017(Barbera et al , 2019 proved useful not only in considering the actions and Fig. 1 Governmental financial resilience, dimensions and relationships (Barbera et al 2017;Steccolini et al 2018) reactions to shocks and crises but also in capturing the capacities needed to cope.…”
Section: Evolution Of (Empirical) Financial Resilience Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the relation between cutback strategies and organizational capacities has been assessed primarily in the European context, which makes it challenging to determine whether the effects observed in these studies result from cutback management itself or other contexts to which public managers were exposed that are specific to the region. For example, using data from local governments in Germany, Italy, and the U.K., Barbera et al (2019) suggest the importance of developing wider organizational capacities in local governments as a key element of effective coping mechanisms in times of crisis. Further, given the U.S. Congressional Budget Office's estimate that domestic programs were cut by 8% as a result of the enactment of the Budget Control Act of 2011 and Consolidated Appropriations Act of 2012 (Newbold, 2017), conducting empirical research on cutback strategies and its effects on organizational capacities in the U.S. context is particularly important.…”
Section: Empirical Studies On Cutback Strategies and Organizational Cmentioning
confidence: 99%